Review articleVariant CJD (vCJD) and Bovine Spongiform Encephalopathy (BSE): 10 and 20 years on: part 1 - Bradley, Ray; Collee, J. Gerald; Liberski, Paweł P. (Folia Neuropathologica, 2006)
From 1986 more than 184,000 cattle in the UK and islands (of which >1,880 have been detected by active surveillance using rapid tests) and approaching 5,500 elsewhere have been confirmed with BSE. The original 1988 ban on the use of ruminant-derived protein in ruminant feed has been upgraded and now prohibits the use of any processed animal protein in feed for any farmed food animal. As a result of rigorous enforcement this reinforced ban is now regarded as fully effective from 1 Aug. 1996. Reasons are given for the substantial slippage that occurred initially and for the small but diminishing number of cases that have occurred in cattle born after 1 Aug. 1996. The 1989 offal ban, initially introduced to protect public health, has likewise been progressively strengthened and since 1995 has been effectively enforced by the Meat Hygiene Service, thus protecting the consumer. It is now extended as the specified risk material (SRM) ban throughout the EU. BSE continues to decline towards elimination in the UK and is being dealt with effectively in other Member States of the European Union (EU) and Switzerland with an extensive (and very expensive) range of edicts. The improving situation in the EU has encouraged the EC to draft a TSE Roadmap outlining possible reduction in control measures whilst still protecting the consumer. The situation on a global basis still causes concern as, although cases are less frequent than in the UK, surveillance, legislation and enforcement are not clearly as extensive and effective as in the EU. The risk of primary transmission of BSE to man from cattle to cause variant CJD (vCJD) is examined with reference to up-to-date assessments of bovine tissue infectivity and is now regarded as unlikely in the EU and Switzerland.